A Green, Facile Approach for the Multicomponent Synthesis of Bioactive Spiro[Indoline-3, 7′-Pyrrolo[1, 2-c]Imidazole] Derivatives. (February 2015) - Shen, Tianhua; Zhou, Yongbing; Che, Fengfeng; Yu, Jiangxia; Lin, Yan; Song, Qingbao
An efficient synthesis of spiro[indoline-3, 7′-pyrrolo[1, 2-c]imidazole] is achieved through a three-component reaction of isatins, malononitrile, and hydantoin/2-thiohydantoin in water catalysed by NaHCO3 . All the target compounds were screened for the Cell Division Cycle 25 Phosphatase B (CDC25B) inhibitory activities.